Elevation of preoperative serum hs-CRP is an independent risk factor for malnutrition in patients with gastric cancer - Mao, Yuantian; Liu, Jinlu; Li, Jiaming; Qiu, Yue; Wang, Zhen; Li, Bopei; Liu, Siyu; Tian, Lei; Chen, Junqiang (Frontiers in Oncology, 2023)
Background: Recent studies have reported hypersensitive C-reactive protein (hs-CRP) linked to clinicopathological characteristics and nutritional status of the tumor, but its clinical significance in GC remains unclear. This study aimed to investigate the relationship between preoperative serum hs-CRP level and clinicopathological features and nutritional status in gastric cancer (GC) patients. Methods: The clinical data of 628 GC patients who met the study criteria were analyzed retrospectively. The preoperative serum hs-CRP level was divided into two groups (<1 mg/L and ≥1 mg/L) to evaluate clinical indicators. Nutritional Risk Screening and nutritional assessment of GC patients were performed by the Nutritional Risk Screening 2002 (NRS2002) and the Patient-Generated Subjective Global Assessment (PG-SGA), respectively.The data were subjected to chi-square test, univariate and multivariate logistic regression analyses, respectively. Results: The analysis of 628 GC cases revealed that 338 patients (53.8%) were on malnutrition risk(NRS2002≥3 points), and 526(83.8%) had suspected/moderate to severe malnutrition(PG-SGA≥ 2 points). Preoperative serum hs-CRP level was significantly correlated with age, tumor maximum diameter (TMD), peripheral nerve invasion (PNI), lymph-vascular invasion (LVI), depth of tumor invasion (DTI), lymph node metastasis (LNM), pTNM stage, body weight loss (BWL), body mass index (BMI), NRS2002 score, PG-SGA grade, hemoglobin (HB), total protein (TP), albumin (ALB), prealbumin (PAB) and total lymphocyte count (TLC). Multivariate logistic regression analysis revealed that hs-CRP (OR=1.814, 95%CI=1.174-2.803; P=0.007), age, ALB, BMI, BWL and TMD were independent risk factors for existing malnutritional risk in GC. Similarly, non-malnutrition and suspected/moderate to severe malnutrition groups presented that hs-CRP (OR=3.346, 95%CI=1.833-6.122; P< 0.001), age, HB, ALB, BMI and BWL were independent risk factors for malnutrition in GC. Conclusion: In addition to the generally used nutritional evaluation indicators such as age, ALB, BMI, and BWL, the hs-CRP level may be used as a nutritional screening and evaluation indicator for GC patients.